Stakeholder management in university fundraising projects - Adams, Deidre (Department of Construction Economics and Management, 2020)
The systematic, downward trend in state funding support to public higher education has resulted in many higher education institutions undertaking large-scale, coordinated fundraising projects or capital campaigns in order to increase third stream income. There is a dearth of research which explores stakeholder management – one of the key knowledge areas in project management – in the public higher education fundraising environment. This research study set out to identify the issues which need to be considered when developing a stakeholder management strategy for fundraising projects at a South African public higher education institution. A qualitative, case study approach was adopted, with semi-structured interviews used to obtain the data. Thematic analysis was used for identifying and analysing patterns or themes within data. The University of Cape Town (UCT) was selected as the case. The research identified that there are a number and variety of stakeholders in the UCT fundraising environment. This could give rise to project complexity affecting the stakeholder landscape. The research highlighted there was a main focus on internal stakeholders, as well as certain external stakeholders necessary for providing third stream income to the university. Some of the strategies used to manage stakeholders were also those identified as critical success factors for effective stakeholder management. The research highlighted the importance of relationship management and stewardship as stakeholder management strategies, which supports the normative approach of stakeholder management. The study found that internal stakeholders possibly cause uncertainty in projects, and hence stakeholder management strategies could mitigate against the possible negative effects.